New Approach for Test Quality Evaluation Based on Shannon Information Measures - Haroutunian, Mariam E.; Avetisyan, Varazdat K. (Mathematical Problems of Computer Science, 2021)
There are two currently popular statistical frameworks for addressing test data analyzing: Classical Test Theory (CTT) and Item Response Theory (IRT). Each of these approaches has its advantages and disadvantages. The detailed description of CTT was given in the previous paper of V. K. Avetisyan [1]. In this paper the description of IRT models are provided to show the complex mathematical apparatus used. In this investigation we suggest a new model of test quality evaluation based on information measures such as Shannon entropy, conditional entropy and average mutual information.We show that this approach is easier and more informative.